TGFβ2 Regulates Human Trabecular Meshwork Cell Contractility via ERK and ROCK Pathways with Distinct Signaling Crosstalk Dependent on the Culture Substrate. (3rd August 2022) - Li, Haiyan; Henty-Ridilla, Jessica L.; Bernstein, Audrey M.; Ganapathy, Preethi S.; Herberg, Samuel
Abstract: Purpose: Transforming growth factor-beta 2 (TGFβ2) is a major contributor to the pathologic changes occurring in human trabecular meshwork (HTM) cells in primary open-angle glaucoma (POAG). TGFβ2 activates extracellular-signal-regulated kinase (ERK) and Rho-associated kinase (ROCK) signaling pathways, both affecting HTM cell behavior. However, exactly how these signaling pathways converge to regulate HTM cell contractility is unclear. Here, we investigated the molecular mechanism underlying TGFβ2-induced pathologic HTM cell contractility, and the crosstalk between ERK and ROCK signaling pathways with different culture substrates. Methods: Hydrogels were engineered by mixing collagen type I, elastin-like polypeptide, and hyaluronic acid, each containing photoactive functional groups, followed by UV crosslinking. Primary HTM cells were seeded atop pre-formed hydrogels for comparisons with glass, or encapsulated within the hydrogels. Changes in actin cytoskeleton, extracellular matrix (ECM) production, phospho-myosin light chain (p-MLC) levels, and hydrogel contraction were assessed. Results: HTM cell morphology and filamentous (F)-actin organization were affected by the underlying culture substrates. TGFβ2 increased HTM cell contractility via ERK and ROCK signaling pathways by differentially regulating F-actin, α-smooth muscle actin (αSMA), fibronectin (FN), and p-MLC in HTM cells. ERK inhibition, even as short as 4 h, further increased TGFβ2-induced p-MLC in HTM cells on hydrogels, but not on glass. This translated into hypercontractility of HTM cell-laden hydrogels. ROCK inhibition had precisely the opposite effects and potently relaxed the TGFβ2-induced hydrogels. Conclusions: Our data suggest that ERK signaling negatively regulates ROCK-mediated HTM cell contractility. These findings emphasize the critical importance of using tissue-mimetic ECM substrates for investigating HTM cell physiology and glaucomatous pathophysiology in vitro .